Impact of antibiotic resistance on outcomes of neutropenic cancer patients with Pseudomonas aeruginosa bacteraemia (IRONIC study): study protocol of a retrospective multicentre international study. Issue 5 (24th May 2019) - Albasanz-Puig, Adaia; Gudiol, Carlota; Parody, Rocío; Tebe, Cristian; Akova, Murat; Araos, Rafael; Bote, Anna; Brunel, Anne-Sophie; Calik, Sebnem; Drgona, Lubos; García, Estefanía; Hemmati, Philipp; et al.
Abstract : Introduction: Pseudomonas aeruginosa (PA) has historically been one of the major causes of severe sepsis and death among neutropenic cancer patients. There has been a recent increase of multidrug-resistant PA (MDRPA) isolates that may determine a worse prognosis, particularly in immunosuppressed patients. The aim of this study is to establish the impact of antibiotic resistance on the outcome of neutropenic onco-haematological patients with PA bacteraemia, and to identify the risk factors for MDRPA bacteraemia and mortality. Methods and analysis: This is a retrospective, observational, multicentre, international study. All episodes of PA bacteraemia occurring in neutropenic onco-haematological patients followed up at the participating centres from 1 January 2006 to 31 May 2018 will be retrospectively reviewed. The primary end point will be overall case-fatality rate within 30 days of onset of PA bacteraemia. The secondary end points will be to describe the following: the incidence and risk factors for multidrug-resistant and extremely drug-resistant PA bacteraemia (by comparing the episodes due to susceptible PA with those produced by MDRPA), the efficacy of ceftolozane/tazobactam, the rates of persistent bacteraemia and bacteraemia relapse and the risk factors for very early (48 hours), early (7 days) and overall (30 days) case-fatality rates. Ethics and dissemination: The Clinical Research Ethics Committee of Bellvitge University Hospital approved the protocol of the study at the primary site. To protect personal privacy, identifying information of each patient in the electronic database will be encrypted. The processing of the patients' personal data collected in the study will comply with the Spanish Data Protection Act of 1998 and with the European Directive on the privacy of data. All data collected, stored and processed will be anonymised. Results will be reported at conferences and in peer-reviewed publications.